Paper-based microfluidic devices based on 3D network polymer hydrogel for the determination of glucose in human whole blood. Issue 56 (10th October 2019) - He, Rong-Yu; Tseng, Hsin-Yi; Lee, Hsia-An; Liu, Yu-Ci; Koshevoy, Igor O.; Pan, Sheng-Wei; Ho, Mei-Lin
Abstract : In this study, optical microfluidic paper analytical devices (μPADs) for glucose detection from whole blood samples with a small sample volume (2 μL) have been developed on a single paper. Abstract : In this study, optical microfluidic paper analytical devices (μPADs) for glucose detection from whole blood samples with a small sample volume (2 μL) have been developed on a single paper. In the proposed method, a mushroom-shaped analytical device contains a sample inlet zone and a detection zone. When blood is dripped onto the inlet region of a μPAD, the plasma diffuses to the detection region. The detection region is implanted with a metallic three-dimensional (3D) polymer hydrogel vehicle. The gel vehicle consists of a copper complex that responds to oxygen changes and glucose oxidase (GOx) immobilized inside the gel as a bioactivity preservative. The phosphorescence of the copper complex is enhanced by oxygen consumed by detection of glucose with a limit of detection (S/N = 3) of 0.44 mM, and the total analysis of the sample is completed within 1 min. The validity of the proposed research is demonstrated using control samples and real-world whole blood samples of glucose concentrations ranging from 3 to 200 mM, and the detection results are shown to be in agreement with those obtained using a glucometer. Attaining a simple device for analysing glucose in human whole blood without any pretreatment procedures and having a broad sensing range while consuming a small sample volume remain challenging; thus, our new analytical device is of great interest.